Antioxidant potential of coriander seed extract and its amelioration of liver antioxidant enzymes by CCl4 induced toxicity in rats - S, Naveen; Khanum, Farhath (International Journal of Pharmaceutical & Biological Archive, 2010)
Coriander seeds have the ability to work as an antioxidant and its efficiency in countering the chemically induced oxidative stress is well established. But no work on its effect on carbon tetrachloride (CCl4) induced toxicity has been reported so far. In this study the effect of coriander seed extract on CCl4 induced lipid peroxidation, oxidative stress and activities of phase II enzymes has been investigated. Coriander seed extract (0.5 and 1% incorporated diets) were fed to rats followed by CCl4 injection (3ml/kg body wt, i.p.) at the end of 30days feeding period. CCl4 induced oxidative stress by increasing lipid peroxidation (by 764%), depleting glutathione levels (by 43.59%), reducing the activities of antioxidant enzymes viz., catalase by 29%, superoxide dismutase by 34%, glutathione peroxidase by 52% and increasing the activity of g-glutamyl transpeptidase by 245%. However, in the group of rats pre-fed with coriander seed extract, the CCl4 induced toxicity was significantly ameliorated. The spice reduced lipid peroxidation (by 300-600%) and increased the antioxidant enzyme activities (catalase by 55-75%, superoxide dismutase by 57-62% and glutathione peroxidase by 80-83%) reducing liver damage. In conclusion, coriander seed extract could minimize the drug induced oxidative stress and protected the system against its toxicity.